2021
DOI: 10.1111/ijcp.14698
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dehydroepiandrosterone (DHEA) supplementation on cortisol, leptin, adiponectin, and liver enzyme levels: A systematic review and meta‐analysis of randomised clinical trials

Abstract: Dehydroepiandrosterone (DHEA) and its sulphated derivative, DHEA sulphate (DHEA-S), are among the most plentiful hormones in human beings. 1 DHEA is an adrenal hormone that has an essential role as a precursor to the peripheral biosynthesis of androgens and oestrogens. 2 Physiologically, DHEA concentrations typically climax in the third decade of life and then gradually decrease thereafter. 1,2 DHEA is also recognised as a "neurosteroid" 3 and its supplementation in elderly people has been linked to many benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…We speculate that the correlation between DHEA and BMI might only exist in special populations, such as patients with metabolic syndrome and type 2 diabetes mellitus. As Chen et al 9 . showed that DHEA can improve the metabolic profile associated with adipose tissue without affecting liver function, it remains to be shown whether diseases are included in special populations.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We speculate that the correlation between DHEA and BMI might only exist in special populations, such as patients with metabolic syndrome and type 2 diabetes mellitus. As Chen et al 9 . showed that DHEA can improve the metabolic profile associated with adipose tissue without affecting liver function, it remains to be shown whether diseases are included in special populations.…”
Section: Discussionmentioning
confidence: 99%
“… 19 confirmed through animal experiments that some mechanisms leading to the occurrence and progression of DN have been triggered, such as inflammation, fibrosis and the expression of stress response mediators, before kidney damage occurs in the early stage of diabetes 4 , 15 . As a common steroid hormone, the level of DHEA decreases with age 1 , 9 , 20 . It can alleviate or even inhibit the progression of some age‐related diseases 9 , 17 , which might be related to its anti‐oxidant properties 21 , 22 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations